2012
DOI: 10.1111/j.1600-0536.2012.02084.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing aluminium contact allergy

Abstract: The results of this study indicate that patch testing with aluminium chloride hexahydrate 2.0%, with an empty Finn Chamber® and the intradermal test with the salt and doses used are insufficient methods to detect contact allergy to aluminium. Aluminium chloride hexahydrate at 10.0% gave the highest number of positive reactions to aluminium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 29 publications
2
45
1
Order By: Relevance
“…is a more sensitive way of diagnosing aluminium hypersensitization than patch testing with metallic aluminium in terms of an empty Finn Chamber. Similar results have been obtained in other studies . Salik et al reported the testing of 42 children with itching nodules after vaccination, 40 of whom had positive results.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…is a more sensitive way of diagnosing aluminium hypersensitization than patch testing with metallic aluminium in terms of an empty Finn Chamber. Similar results have been obtained in other studies . Salik et al reported the testing of 42 children with itching nodules after vaccination, 40 of whom had positive results.…”
Section: Discussionsupporting
confidence: 84%
“…This was a retrospective study, and it is noteworthy that, among those children with persistent skin reactions, 95% were positive for aluminium, and they were all < 10 years of age when tested. Siemund et al tested 21 adults, aged 21 to 71 years, with a mean age of 46 years, with 6 different aluminium compounds, including 2% and 10% aluminium chloride hexahydrate pet., and an empty Finn Chamber, and 19 reacted to at least 1 of the aluminium salts, but none reacted to the metallic aluminium disc. They also reported that 10% aluminium chloride hexahydrate pet.…”
Section: Discussionmentioning
confidence: 99%
“…is insufficient to detect contact allergy to aluminium. 25 In contrast, our experience of patch testing children with aluminium in the three studies mentioned above (A-C) was that very high proportions (74%, 86%, and 85%, respectively) not only reacted positively, but often also reacted strongly to aluminium chloride hexahydrate 2% pet. 4,5,13,14 This is consistent with a Danish study by Salik et al, in which 39 of 42 children with vaccine-induced persistent pruritic subcutaneous nodules aged 3 months to 6 years reacted positively to aluminium chloride hexahydrate 2% pet.…”
Section: Introductionmentioning
confidence: 89%
“…Patch testing has been the gold standard for diagnosing contact allergy since Jadassohn introduced his ‘application method’ in 1895 . Many studies were performed in order to optimize the patch test procedure, and today it is a well‐standardized method .…”
mentioning
confidence: 99%
“…At our department, we patch tested aluminium‐allergic individuals with different aluminium test preparations in order to find an optimal aluminium compound and an opimal test concentration . In that previous study, 2 of 21 participants did not show any skin reaction.…”
mentioning
confidence: 99%